Death, sex and fertility: Female infanticide in rural Spain, 1750-1950 - Francisco J. Beltrán Tapia; Francisco J. Marco-Gracia (European Historical Economics Society (EHES), 2020)
Relying on longitudinal micro data from a Spanish rural region between 1750 and 1950, this article evidences that families mortally neglected a significant fraction of their female babies. On the one hand, baptism records exhibit exceptionally high sex ratios at birth, especially during the 19th century. On the other hand, our data shows that having no previous male siblings increased both the probability of male baptisms and female mortality during the first day of life. These findings seem to be concentrated at higher parities and among landless and semi-landless families which were subject to harsher economic conditions and therefore more likely to resort to extreme decisions under difficult circumstances. Crucially, the fact that the results are robust to employing data from birth and death registers rules out the possibility that under-registration explains this pattern. Lastly, although these practices were definitely more important during the traditional demographic regime, discriminatory patterns affecting female mortality shortly after birth were still visible during the first decades of the 20th century, thus proving that son preference continued to be a strong cultural norm within these societies.
Keywords: I14; I15; J13; J16; N33; 330; Sex ratios; Infant mortality; Infanticide; Gender discrimination